The study of 1,2-propanediol influence on red cell membranes by method of fluorescent probes - Корнієнко, Є. М.; Посохов, Є. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The influence of cryoprotectant 1,2-propanediol on human red cell membranes has been studied by use of the set of fluorescent probes – orto-hydroxy derivatives of oxazole and oxadiazole. It has been shown that fluorescent probes on the base of ortho-hydroxy derivatives of oxazole can be used as indicators of the changes of physico-chemical properties and structure of red cell membranes under the action of 1,2-propanediol: it has been found that the initial concentration of 1,2-propanediol, which causes the changes in the structure of human red cell membranes, is 5 vol.%. It has been shown that under the influence of 1,2-propanediol the changes occur in polar regions of the membranes, while no changes occur in hydrophobic regions of red cell membranes. The obtained findings may be useful for choice of optimal conditions for cryoprotecting.